Challenging the patriarchy: radical feminist themes in 'The Yellow Wallpaper' - Nurhayati Purba; Kokardi, Ella Meidelin; Gihon Kusy Marpaung; Devi Tania Panjaitan (Institut Agama Islam Negeri Palopo, 2024)
The main factor causing inequality for women is patriarchy. As in many old-school traditions, patriarchy remains in marriage where wives are urged to bow down to their husbands and the husband is regarded as the ultimate authority of the household. This research investigates the narrative of Charlotte Perkins Gilman's iconic short story,